Isolation and characterization of ɸEcM-vB1 bacteriophage targeting multidrug-resistant Escherichia coli - Rania Abozahra; Dina Shlkamy; Sarah M. Abdelhamid (BMC Research Notes)
Abstract Objectives The aim of this study is to screen for, isolate and characterize a bacteriophage designated ɸEcM-vB1 with confirmed lytic activity against multidrug-resistant (MDR) E. coli. Methods done in this research are bacteriophage isolation, purification, titer determination, bacteriophage morphology, host range determination, bacteriophage latent period and burst size determination, genomic analysis by restriction enzymes, and bacteriophage total protein content determination. Results ɸEcM-vB1 bacteriophage exhibited high lytic activity against different MDR E. coli isolates and showed stability over wide pH and temperature range. It belongs to the Myoviridae family of the caudovirales order according to TEM. It had a latent period of 5 min and an average burst size of 271.72 pfu/cell. Genomic analysis revealed that it is susceptible to digestion by EcoRI. Ten structural proteins were detected by SDS-PAGE. ɸEcM-vB1 is considered a promising candidate for phage therapy applications.